THE EFFECT OF SALINITY ON GROWTH, HORMONES AND MINERAL ELEMENTS IN LEAF AND FRUIT OF TOMATO CULTIVAR PKM1 - M. A. Babu; D. Singh; K. M. Gothandam (Journal of Animal and Plant Sciences, 2012)
Tomato cultivar PKM 1 were subjected to 25, 50, 100, 150 and 200 mM NaCl stress and response of tomato plant to salt stress were determined by assessing the variability of different biochemical parameters. In this present study endogenous content of growth hormones IAA and ABA in leaves, proline and mineral (Na+ and K+) content in leaves and mature fruits were estimated. Leaf area and dry matter content of tomato fruits under salt stress were determined to study the effect of salinity on photosynthetic yield. Results showed that leaf area and dry matter content of tomato fruits decreased with application of elevated salt stress, however endogenous content of IAA, ABA and proline was found to be increasing with increase in salt treatment. Application of NaCl caused increase in Na+ content, while K+ content and K+/Na+ ratio decreased with increase in salt stress. Another striking point is that increase in proline and Na+ content was more in leaves than fruits, which suggests that leaves are more sensitive than fruits.
Keywords: Salt stress; IAA; ABA; Proline; Na+; dry matter